The mechanism of a high-affinity allosteric inhibitor of the serotonin transporter - Per Plenge (Nature Portfolio, 2020)
The serotonin transporter (SERT) terminates serotonin signaling and its activity is modulated by antidepressants. Here authors reveal the mechanistic details underlying the coupling between the two binding sites in SERT and a high-affinity ligand for the allosteric site.